KARAKTERISTIK BEBERAPA SIFAT KIMIA DAN FISIK TANAH PADA AREAL PERTANAMAN CENGKEH (SyzigiumaromaticumL.) DI DATARAN RENDAH DEKAT PANTAI DESA TUDUA KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Ulva, Ulva; Thaha, Abd. Rahim; Wahyudi, Imam (AGROTEKBIS, 2018)
This study aims to determine the characteristics of some chemical and physical properties of soil on clove plants in the lowland. This research was conducted in Tudua Village, Central Bungku District,Morowali District from March till May 2017. Analysis of some soil chemical properties was done at Soil Science Laboratory of Agricultural Faculty of Tadulako University Palu. The method used in this research is survey method,while Determination of research location conducted in parallel (purposive sampling) and soil sampling was done systematically with grid system at 15 x 15 m distance adjusted to condition of survey area. Soil samples were taken from 3 clove plantation locations, each clove plantation location was collected in 3 sub samples and then composed, so that 3 composite soil samples were obtained to be analyzed in the laboratory. The observed variables to be analyzed are soil chemical properties including pH, C-Organic, CEC, N, P, K, and Ca while soil physical properties include soil texture, bulk density, soil porosity, soil permeability and color of soil. The results showed that soil chemical properties of the three clove plantation sites had very acid pH, sour to slightly acid, C-Organic had moderate to high criterion, CEC and N criteria were moderate to high, K and Ca had very low criteria. While the soil physical properties of the three clove plantation sites have sandy clay texture class to sandy clay, moderate to high soil BD, porosity with poor criteria to good, permeability tend to be medium to fast, and soil color is diverse where there is a dark yellowish brown color, brown to dark brown.